Autophagy Induces Expression of IL-6 in Human Periodontal Ligament Fibroblasts Under Mechanical Load and Overload and Effects Osteoclastogenesis in vitro - Mayr, Alexandra; Marciniak, Jana; Eggers, Benedikt; Blawat, Kim; Wildenhof, Jan; Bastos Craveiro, Rogerio; Wolf, Michael; Deschner, James; Jäger, Andreas; Beisel-Memmert, Svenja (Frontiers in Physiology, 2021)
Objective: Autophagy is an important cellular adaptation mechanism to mechanical stress. In animal experiments, inhibition of autophagy during orthodontic tooth movement triggered increased expression of inflammation-related genes and decreased bone density. The aim of this study was to investigate how autophagy affects cytokine levels of interleukin 6 (IL-6) in human periodontal ligament (hPDL) fibroblasts under mechanical pressure and the resulting influence on osteoblast communication. Methods: hPDL fibroblasts were subjected to physiologic mechanical load, constant overload, or rapamycin treatment for 16 to 24 h ± autophagy inhibitor 3-MA. Autophagosomes were quantified by flow cytometry. Gene expression of il-6 as well as IL-6 levels in the supernatant were determined with rtPCR and ELISA. To investigate the influence of mechanically-induced autophagy on cell-cell communication, an osteoblast-culture was subjected to supernatant from stimulated hPDL fibroblasts ± soluble IL-6 receptor (sIL-6R). After 24 h, osteoprotegerin (opg) and receptor activator of nuclear factor κB ligand (rankl) gene expressions were detected with rtPCR. Gene expression of a disintegrin and metalloproteinases (adam) 10 and 17 in stimulated hPDL fibroblasts was examined via rtPCR. Results: Autophagy was induced by biomechanical stress in hPDL fibroblasts in a dose-dependent manner. Mechanical load and overload increased IL-6 expression at gene and protein level. Autophagy inhibition further enhanced the effects of mechanical stimulation on IL-6 expression. Mechanical stimulation of hPDL fibroblasts downregulated adam10 and adam17 expressions. Inhibition of autophagy had stimulus-intensity depending effects: autophagy inhibition alone or additional application of physiological stress enhanced adam10 and adam17 expressions, whereas mechanical overload had adverse effects. Osteoblasts showed significantly reduced opg expression in the presence of supernatant derived of hPDL fibroblasts treated with autophagy inhibitor and sIL-6R. Conclusion: IL-6 levels were increased in response to pressure in hPDL fibroblasts, which was further enhanced by autophagy inhibition. This caused a decrease in opg expression in osteoblasts. This may serve as an explanatory model for accelerated tooth movement observed under autophagy inhibition, but may also represent a risk factor for uncontrolled bone loss.